An improved Theileria parva sporozoite seroneutralization assay for the identification of East Coast fever immune correlates - Chege, Hannah; Githigia, S.; Gathumbi, J.; Chege, Naomi; Ojuok, Rose; Odaba, Josiah; Mwalimu, Stephen; Oboge, Harriet; Steinaa, Lucilla; Nene, Vishvanath; Lacasta, Anna (MDPI, 2024)
Background: Immune correlates of protection are ideal tools to predict treatment or vaccine efficacy. However, the accuracy of the immune correlate and the capability to robustly predict the outcome of a vaccine candidate are determined by the performance of the in vitro immunoassay used. Several Theileria parva sporozoite seroneutralization assays have previously been used to assess antibody functional activities; however, a common limitation has been the need for fresh material, target cells and sporozoites, and operator-to-operator bias. An improved assay represents a positive step toward overcoming challenges associated with variability and it might provide a more reliable means of establishing an immune correlate with protection after sub-unit vaccine administration.